Social Interaction and Religious Harmony: A Cultural Communication Study in Malaka Regency, East Nusa Tenggara - Maesurah, Sitti; Klau, Stanis; Cangara, Hafied; Nurdiantara, Robby Rachman (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study examines the dynamics of social interaction and religious harmony between Bugis migrant communities and local residents in Malaka Regency, East Nusa Tenggara. Employing a descriptive qualitative approach through in-depth interviews and participant observation, the research identifies key factors that foster social cohesion amid ethnic and religious diversity. Data analysis draws on Integrative Communication Theory and Anxiety and Uncertainty Management Theory. The findings reveal that effective cultural adaptation, open intercultural communication, and the practice of inclusive religious values serve as the primary foundations for maintaining social harmony. The adaptation process unfolds through collaborative, two-way communication in which both groups learn from one another and demonstrate respect for cultural differences. In addition, spiritual values promoted by religious leaders function as a shared ethical framework that reinforces interfaith solidarity. The resulting acculturation is reciprocal, leading to the formation of a new social identity grounded in mutual respect and cooperation. This study affirms that empathetic intercultural communication shaped by religious values can support a sustainable model of social harmony in multiethnic societies. The findings contribute to the literature on cross-cultural communication and offer insights for the development of social policies in the pluralistic contexts of Eastern Indonesia.